Waqf Crowdfunding Model in Post-Pandemic Economic Improvement According to Islamic Sharia and National Law - Sulistiani, Siska Lis; Fawzi, Ramdan; Nurrachmi, Intan (Univeristas Islam Bandung, 2023)
Technological developments make waqf able to be developed in terms of socialization, fundraising, and management in an effort to improve the economy after the COVID-19 pandemic. This study aims to identify and analyze the waqf crowdfunding model for post-pandemic economic improvement according to Islamic law and national law. This research is qualitative with a normative juridical approach, using types and sources of legal data including primary legal sources, Law No. 41 of 2004 concerning Waqf, PP No. 42 of 2006, and other regulations. In terms of Islamic sharia, namely the Al-Quran, Al-hadith, fatwas, and the opinions of related scholars, Secondary legal sources are journals, proceedings, theses, dissertations, and books, while tertiary legal sources are interviews with crowdfunding managers and nadzhir waqf. Then the data is collected through library research and then analyzed to see the synchronization stage and conformity with legal norms and principles through descriptive analysis.